Circulating follistatin concentrations in adolescent PCOS: Divergent effects of randomized treatments - Díaz, Marta; de Zegher, Francis; Ibáñez, Lourdes (Frontiers in Endocrinology, 2023)
Purpose Follistatin is a glycoprotein that represses members of the transforming growth factor-β superfamily including activin. Higher follistatin levels have been associated with an increased risk for type 2 diabetes and with polycystic ovary syndrome (PCOS). In non-obese adolescent girls with PCOS, insulin sensitization results in a healthier endocrine-metabolic outcome than oral contraception (OC); we assessed whether those differences are underscored by changes in serum follistatin concentrations. Methods Circulating follistatin, endocrine-metabolic markers and hepato-visceral fat were measured longitudinally in 72 girls with PCOS [age, 16 years; body mass index (BMI), 23 Kg/m2] randomized to receive PioFluMet [pioglitazone (7.5 mg/d), metformin (850 mg/d) and flutamide (62.5 mg/d), n=17]; EE-CA [an OC containing 35 µg ethinylestradiol (EE) and 2 mg cyproterone acetate (CA), n=17]; SPIOMET [Spironolactone (50 mg/d), pioglitazone (7.5 mg/d) and metformin (850 mg/d), n=18], or EE-LNG [an OC containing 20 µg EE and 100 mg levonorgestrel (LNG), n=20]. Twenty-eight age- and BMI-matched healthy girls served as controls. Results Pre-treatment follistatin levels were similar in PCOS and controls. OCs raised serum follistatin after 6 months (6.8-fold vs 2.5-fold for EE-CA and EE-LNG, respectively). Neither SPIOMET nor PioFluMet changed follistatin levels. Follistatin correlated negatively with high-molecular weight adiponectin and positively with mean serum insulin concentrations during an oral glucose tolerance test at baseline, and with liver fat after 6 months. Conclusion In girls with PCOS, follistatin levels rise significantly after 6 months on OCs and this increase associates to a worsening of markers of insulin resistance and to changes in liver fat.